2014
DOI: 10.3390/ijms151121401
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Increases Adiponectin Secretion from Differentiated Bovine Preadipocytes through G-Protein Coupled Receptor Signaling

Abstract: The transition period in dairy cows (3 weeks prepartum until 3 weeks postpartum) is associated with substantial mobilization of energy stores, which is often associated with metabolic diseases. Nicotinic acid (NA) is an antilipolytic and lipid-lowering compound used to treat dyslipidaemia in humans, and it also reduces non-esterified fatty acids in cattle. In mice the G-protein coupled receptor 109A (GPR109A) ligand NA positively affects the secretion of adiponectin, an important modulator of glucose and fat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Thus we assume that HCAR2 is regulated through PPARG rather than by its endogenous ligand BHBA. Friedrichs, Sauerwein, Huber, Locher, Rehage, Meyer, Dänicke, Kuhla and Mielenz This assumption is in line with the study of Kopp et al (2014) in which the mRNA abundance of HCAR2 was not downregulated in bovine adipocytes in vitro by uncoupling of G-protein signalling using pertussis toxin.…”
Section: Changes In Hcar2 Expressionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus we assume that HCAR2 is regulated through PPARG rather than by its endogenous ligand BHBA. Friedrichs, Sauerwein, Huber, Locher, Rehage, Meyer, Dänicke, Kuhla and Mielenz This assumption is in line with the study of Kopp et al (2014) in which the mRNA abundance of HCAR2 was not downregulated in bovine adipocytes in vitro by uncoupling of G-protein signalling using pertussis toxin.…”
Section: Changes In Hcar2 Expressionsupporting
confidence: 67%
“…Due to its function as metabolic sensor suppressing lipolysis during starvation, HCAR2 is an important target for a group of antilipolytic drugs (Offermanns et al, 2011). We recently reported that the HCAR2 ligand niacin stimulates the expression of HCAR2 in differentiated bovine preadipocytes in vitro (Kopp et al, 2014). Comparable to other mammalian species, the retroperitoneal AT (RPAT) from dairy cattle seems to have a higher lipolytic activity than subcutaneous AT (SCAT) due to the higher expression of hormone-sensitive lipase and the greater lipolytic response to adrenergic stimulation in RPAT (Locher et al, 2011;Kenéz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Forty hours posttransfection, the cells were induced to differentiation, with the first differentiation media supplemented with 0.5 mM hydrocortisol, IBMX (3.isobutyl‐1‐methylxanthine), dexamthasone 1 μM, and insulin 167 nM as described previously (Kopp et al, 2014). After 2 days, the cells were induced to differentiation with second differentiation medium containing DMEM‐F/12 medium with 10% fetal bovine serum and insulin 167 nM.…”
Section: Methodsmentioning
confidence: 99%
“…Forty hours posttransfection, the cells were induced to differentiation, with the first differentiation media supplemented with 0.5 mM hydrocortisol, IBMX (3.isobutyl-1-methylxanthine), dexamthasone 1 μM, and insulin 167 nM as described previously (Kopp et al, 2014).…”
Section: Cell Differentiation and Oil Red O Stainingmentioning
confidence: 99%
“…WISP1 fosters nuclear trafficking and activity of SIRT1 that results in neuronal protection and blocks apoptotic injury . WISP1 also regulates the post‐translational phosphorylation of AMPK . WISP1 modulates AMPK activation by differentially decreasing phosphorylation of TSC2 at serine 1387 , a target of AMPK, and increasing phosphorylation of TSC2 at threone 1462 , a target of Akt .…”
Section: Mtor Pathways Of Apoptosis and Autophagymentioning
confidence: 99%